The diffuse ionized gas (DIG) in star-forming galaxies: the influence of aperture effects on local H ii regions. Issue 2 (20th September 2021) - Mannucci, F; Belfiore, F; Curti, M; Cresci, G; Maiolino, R; Marasco, A; Marconi, A; Mingozzi, M; Tozzi, G; Amiri, A
ABSTRACT: The diffuse ionized gas (DIG) contributes to the nebular emission of galaxies, resulting in emission line flux ratios that can be significantly different from those produced by H ii regions. Comparing the emission of [SII]λ6717, 31 between pointed observations of H ii regions in nearby galaxies and integrated spectra of more distant galaxies, it has been recently claimed that the DIG can also deeply affect the emission of bright, star-forming galaxies, and that a large correction must be applied to observed line ratios to recover the genuine contribution from H ii regions. Here, we show instead that the e?ect of DIG on the integrated spectra of star-forming galaxies is lower than assumed in previous work. Here we show that, in contrast, aperture effects on the spectroscopy of nearby H ii regions are largely responsible for the observed difference: When spectra of local H ii regions are extracted using large enough apertures while still avoiding the DIG, the observed line ratios are the same as in more distant galaxies. This result is highly relevant for the use of strong-line methods to measure metallicity.